ENT600: Panda printing Shah Alam / Ain Adilla Abd Rahim … [et al.] - Abd Rahim, Ain Adilla; Bronny, Belinda Gabriella; Mohd Faiz, Muhammad Nazran; Lapok, Hafidah; Hamdan, Siti Amira (2018)
Panda Printing Shah Alam is one of the most known printing shops among students. The location of this shop itself which is near university as well as student's house make this shops popular among students. Other than that, this printing shop also offering various services such as photocopies services, printing, flyers, rubber stamp, button badge and more. Even though this shop offered various services, there were few issues that become a concern regarding their business. If this issue does not solve quickly, it will affect their services quality as well as products quality in the future. Regarding to this issue, this case study was conducted in order to determine the problems and analyze any possible solutions.